Guidelines for Genetic Testing and Management of Alport Syndrome. Issue 1 (January 2022) - Savige, Judy; Lipska-Zietkiewicz, Beata S.; Watson, Elizabeth; Hertz, Jens Michael; Deltas, Constantinos; Mari, Francesca; Hilbert, Pascale; Plevova, Pavlina; Byers, Peter; Cerkauskaite, Agne; Gregory, Martin; Cerkauskiene, Rimante; et al.
Abstract : Genetic testing for pathogenic COL4A3–5 variants is usually undertaken to investigate the cause of persistent hematuria, especially with a family history of hematuria or kidney function impairment. Alport syndrome experts now advocate genetic testing for persistent hematuria, even when a heterozygous pathogenic COL4A3 or COL4A4 is suspected, and cascade testing of their first-degree family members because of their risk of impaired kidney function. The experts recommend too that COL4A3 or COL4A4 heterozygotes do not act as kidney donors. Testing for variants in the COL4A3–COL4A5 genes should also be performed for persistent proteinuria and steroid-resistant nephrotic syndrome due to suspected inherited FSGS and for familial IgA glomerulonephritis and kidney failure of unknown cause.